Given:
In a set of 3 numbers the first is a positive integer, the second is 3 more than the first and the 3rd is a square of the second.
To find:
The equation for the given situation if the sum of the numbers is 77.
Solution:
a. Let the first number in the set is x.
The second is 3 more than the first. So, the second number is
.
The 3rd number is a square of the second. So, the third number is
.
Therefore, the first, second and third numbers are
respectively.
b. The sum of the numbers is 77.
First number + Second number + Third number = 77
c. So, the equation in terms of x is:
![x+(x+3)+(x+3)^2=77](https://tex.z-dn.net/?f=x%2B%28x%2B3%29%2B%28x%2B3%29%5E2%3D77)
Therefore, the required equation is
.
d. On simplification, we get
![[\because (a+b)^2=a^2+2ab+b^2]](https://tex.z-dn.net/?f=%5B%5Cbecause%20%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2%5D)
![x^2+(6x+x+x)+(3+9)=77](https://tex.z-dn.net/?f=x%5E2%2B%286x%2Bx%2Bx%29%2B%283%2B9%29%3D77)
![x^2+8x+12=77](https://tex.z-dn.net/?f=x%5E2%2B8x%2B12%3D77)
Subtract 77 from both sides.
![x^2+8x+12-77=77-77](https://tex.z-dn.net/?f=x%5E2%2B8x%2B12-77%3D77-77)
![x^2+8x-65=0](https://tex.z-dn.net/?f=x%5E2%2B8x-65%3D0)
Therefore, the simplified form of the required equation is
.